Targeting autophagy enhances the anticancer effect of artemisinin and its derivatives. Issue 6 (11th April 2019) - Sun, Xin; Yan, Peiyi; Zou, Chang; Wong, Yin‐Kwan; Shu, Yuhan; Lee, Yew Mun; Zhang, Chongjing; Yang, Nai‐Di; Wang, Jigang; Zhang, Jianbin
Abstract: Artemisinin and its derivatives, with their outstanding clinical efficacy and safety, represent the most effective and impactful antimalarial drugs. Apart from its antimalarial effect, artemisinin has also been shown to exhibit selective anticancer properties against multiple cancer types both in vitro and in vivo. Specifically, our previous studies highlighted the therapeutic effects of artemisinin on autophagy regulation. Autophagy is a well‐conserved degradative process that recycles cytoplasmic contents and organelles in lysosomes to maintain cellular homeostasis. The deregulation of autophagy is often observed in cancer cells, where it contributes to tumor adaptation to nutrient‐deficient tumor microenvironments. This review discusses recent advances in the anticancer properties of artemisinin and its derivatives via their regulation of autophagy, mitophagy, and ferritinophagy. In particular, we will discuss the mechanisms of artemisinin activation in cancer and novel findings regarding the role of artemisinin in regulating autophagy, which involves changes in multiple signaling pathways. More importantly, with increasing failure rates and the high cost of the development of novel anticancer drugs, the strategy of repurposing traditional therapeutic Chinese medicinal agents such as artemisinin to treat cancer provides a more attractive alternative. We believe that the topics covered here will be important in demonstrating the potential of artemisinin and its derivatives as safe and potent anticancer agents.